Chaupadi in Nepal and it’s different prespective - Shah, Debi Kumari (Medha: A Multidisciplinary Journal, 2023)
Chhaupadi, the restrictions of menstruating women and girls in Nepal. It is a harmful practice with severe consequences for their health, safety, and dignity. It is a detrimental practice that seriously jeopardizes their safety, dignity, and well-being. This paper explores the multifaceted nature of Chhaupadi, examining the religious justifications used to defend it, alongside the arguments of critics who condemn it as a violation of human rights and a public health crisis. By analyzing perspectives from proponents and opponents, the paper highlights the need for a comprehensive approach to eradicate Chhaupadi. This includes demolishing harmful myths about menstruation, promoting menstrual hygiene education, empowering women and girls and addressing the underlying gender inequality within Nepali society. The paper concludes by emphasizing the importance of integrating the voices of Chhaupadi victims and prioritizing their well-being in the fight for a future free from this discriminatory practice.